MEMPERTAHANKAN TRADISI KEBUDAYAAN SAKURA DAN NYAMBAI DI LAMPUNG BARAT DALAM ERA MODERNISASI - Tashya, Nabila Anas; Mardhotillah, Sifa (FKIP Universitas Lampung, 2025)
Cultural traditions are ancestral heritage that contains the values of local wisdom and community identity. In West Lampung, the Sakura and Nyambai traditions have become an important part of the social and cultural life of the community. However, its existence is increasingly threatened by modernization currents that tend to marginalize local traditions. This article examines the efforts of the people of West Lampung in maintaining the tradition of Sakura and Nyambai in the midst of the challenges of the modernization era. The research was conducted with a qualitative approach, through direct observation and interviews with traditional leaders, cultural actors, and local communities. The results of the study show that the Sakura tradition, which is a symbol of respect for nature, and Nyambai, which represents social interaction in Lampung customs, is still maintained through various adaptations. Conservation efforts involve the integration of local culture in educational activities, performing arts, and cultural festivals. In addition, the role of local governments, cultural communities, and the younger generation is very important in maintaining the existence of this tradition. This article emphasizes the importance of preserving local culture as part of the nation's identity that is able to synergize with modernization without losing traditional values. Tradisi budaya merupakan warisan leluhur yang mengandung nilai-nilai kearifan lokal dan identitas masyarakat. Di Lampung Barat, tradisi Sakura dan Nyambai menjadi bagian penting dari kehidupan sosial dan budaya masyarakat. Namun, keberadaannya semakin terancam oleh arus modernisasi yang cenderung meminggirkan tradisi lokal. Artikel ini mengkaji upaya masyarakat Lampung Barat dalam mempertahankan tradisi Sakura dan Nyambai di tengah tantangan era modernisasi. Penelitian dilakukan dengan pendekatan kualitatif, melalui observasi langsung dan wawancara dengan tokoh adat, pelaku budaya, serta masyarakat setempat. Hasil kajian menunjukkan bahwa tradisi Sakura, yang merupakan simbol penghormatan terhadap alam, dan Nyambai, yang merepresentasikan interaksi sosial dalam adat Lampung, masih dipertahankan melalui berbagai adaptasi. Upaya pelestarian melibatkan integrasi budaya lokal dalam kegiatan pendidikan, seni pertunjukan, dan festival budaya. Selain itu, peran pemerintah daerah, komunitas budaya, serta generasi muda sangat penting dalam menjaga eksistensi tradisi ini. Artikel ini menegaskan pentingnya pelestarian budaya lokal sebagai bagian dari identitas bangsa yang mampu bersinergi dengan modernisasi tanpa kehilangan nilai-nilai tradisional.